'Europe' of populist radical right and the case of Lega of Salvini: pioneer of a 'Parochial Europe'?. Issue 1 (1st January 2022) - Öner, Selcen
ABSTRACT: This article focuses on the 'Europe' of populist radical right parties in general, and the Lega of Matteo Salvini and its perception of Europe in particular. Especially after Brexit, Salvini has emphasized the goal of transforming Europe and taking back Italian sovereignty rather than leaving the EU. His discourse on 'Europe for Europeans' and 'Italy for Italians' represents an exclusive and nativist approach. Before the 2019 elections of the European Parliament, the contestation between many Europes came to the fore while the Lega has become a pioneer for populist radical right parties during the campaign period on behalf of a 'parochial Europe'. This article firstly explains the methodology, conceptual analysis, and analytical framework based on European multiplicity – as thin, thick, parochial, and global Europe. Secondly, it evaluates the 'Others' of parochial Europe, particularly for Lega. Thirdly, it analyses the case of the Lega as the pioneer of parochial Europe before the May 2019 EP elections based on semi-structured, face-to-face, in-depth expert interviews conducted by the author.